A glimpse into Finnish book history - Glosienė, Audronė (Knygotyra, 1995)
The book printing and publishing in Finland in its historical perspective resembles that of other European countries. This contribution presents a review of Finnish book history to Lithuanian reader. The sources were limited by language barrier, and only English articles or their summaries published in Finnish periodicals were used. The publications on Finnish book history published in 1988, when the 500 year anniversary of Finnish book was celebrated, are considered to be of most importance. Some attemps for comparative study of development of Finnish book publishing and that of Lithuania are made. Still the review is not considered to be a detailed and deep analysis of the subject, just its outline. The history of Finnish book printing starts in the year 1488, when the first book for use in Finland written in latin was printed in Germany. Lithuanian book historians are more strict in that sense, and they count the age of Lithuanian book from the first book published in mother-tongue. The Reformer of Finland and the creator of literary Finnish Michael Agricola is characterized as one of outstanding personalities in Finnish cultural history. He was also the author of the first Finnish book (ABCkiria, 1543) published. The first printing press was set up in Finland in 1642, and it was printing house of the first University in Finland, Turku. Some decades later bishop Johannes Gezelius started another printing house which was much more modern than the first one. Gezelius’ merits for education and enlightment of people are emphasized. Impact of Swedish literary, cultural tradition and of Swedish language was great in Finland. Orientation had changed after Finland got autonomy in Russia’s empire, and it was national Finnish in its essence, aims and language. The history of book publishing in the 18th century is presented in short. More detailed is the review of book publishing development in the 19th century, when the activities of Finnish Literary Society and those of commercial publishers started. The main publishing statistics of present times is given in the end of the contribution.